ANÁLISE DA QUALIDADE DE DADOS DO SINAN TB A PARTIR DOS INDICADORES DE AçõES DE VIGILâNCIA DA TUBERCULOSE NO ESTADO DA PARAíBA NO ANO 2006 (Fiep Bulletin - online, 2013)
This study aimed to assess the quality of data from the agravo Tuberculosis in the state of Paraiba, Brazil in the year of 2006. This is a descriptive study of secondary data, with quantitative approach, including specific variables in the sheet Notification / Research and Monitoring Bulletin, with use of Tabwin and Excel spreadsheet for analysis of the data. These data were obtained from the Information System of Agravo Notification-Sinan-TB, the Secretary of State for Health. The results showed inconsistencies in the registry data to generate information that can interfere with operational and epidemiological indicators for the control of agravo, with emphasis on those relating to: TB co-infection / AIDS; Closure of cases with 47% without information, and, revealed the adoption of Schedule I to undue cases of Reingressos and Recurrences and IR scheme for new cases.Concluded that there is an urgent need to improve the quality of data in Sinan / TB. We recommend an effective performance monitoring, evaluation of the actions of the Program for Control of Tuberculosis, may cause a significant leap in the quality of the data, therefore the influence of appropriate indicators for monitoring the operational and epidemiological situation of tuberculosis by the Town, State and Union
Keywords: Notice; Tuberculosis; Information on health